Analisa SWOT dan STP (Segmentasi, Tertarget, Posisi) terhadap Strategi Pemasaran Digital pada Usaha Mikro – Bunda Culinary - Henky Hendrawan (Universitas Medan Area, 2021)
The change of conventional marketing to digital marketing has an impact on the business world, including micro businesses. So that a certain strategy is needed in dealing with digital marketing. SWOT analysis and STP analysis among several other analyzes that can be used to determine a marketing strategy. The purpose of this study is to find an overview of the use of SWOT analysis and STP analysis implemented in micro enterprises, namely 'Bunda Culinary'. SWOT analysis and STP analysis are used in order to see what digital marketing strategies are being pursued by the micro entrepreneur 'Bunda Culinary'. The research method used is a descriptive survey. Data collection techniques in this study were observation and interviews. The results obtained are strategies for digital marketing that are carried out only on the pattern of Relationship Marketing, Word of mouth Marketing, Seasonal Marketing, and Social Media Marketing. Meanwhile, the development towards B2B Marketing and B2C Marketing has not been carried out. And there is also no specific personal or team handling digital marketing.